Deskripsi Diferensiasi Sosial Masyarakat Hindu Di Era Modernisasi Di Kota Mataram - Widana, I Nyoman Murba; Putri, Gusti Ayu Dheananda Sagitha (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
The research article that examines the pattern of social differentiation of Hindu society in Mataram City in responding to modernization is designed in a qualitative descriptive type. Based on the research results, it was found that the pattern of social differentiation of Balinese Hindu society living in Mataram City in responding to the pace of modernization began with changes in the social structure. These social changes were responded to by the process of classifying society based on rights and obligations according to the field of work they are engaged in. This classification is further related to its functionalization in the practice of religious life, namely concerning its role and position in the social structure